Economic Paradigms in the First Half of the 20th Century - Szávai, Ferenc (Acta Scientiarum Socialium, 2015)
Economic Paradigms in the First Half of the 20th Century In examining the economic paradigms of the 20th century we can come to the conclusion that the Great Depression made the biggest economic impact. First and foremost the crisis of the liberal economy during 1929–1933 has induced state intervention into the economy which gave rise to unique ways of recovery from the crisis. Although the economic aftermath of the First World War and the following peace did not mean the greatest economic paradigm, nonetheless three state formations fell victim to it, Russia, the Austro-Hungarian Monarchy and the Ottoman Empireâ€”leaving behind several conflicts together with their resolution attempts.
Keywords: economic history; history of economic thought; World War I; Great Depression